(untitled) (Revista Paradigma, 2020)
The principle of separation of powers has been erected to the stone clause condition and represents one of the means for the realization of the Democratic Rule of Law, so that after the Federal Constitution of 1988, with the expansion of rights, the judiciary becomes more active with the aim of realizing fundamental rights provided for in it, most often not observed by the other powers, leading to debates about the democratic legitimacy of such action by some called judicialization of policy or judicial activism. Thus, starting from the premise that the 1988 constitutional text has normative force and radiates its commands to the entire legal system, as well as from the perspective of neoconstitutionalism, the conceptual breadth of the legal norm in which the principles come to integrate it and the “ unconstitutional state of affairs ”(ECI), to investigate the personality rights of prisoners in Brazil. The aim is to discuss to what extent the “unconstitutional state of affairs” used by the Supreme Federal Court (STF) in the Fundamental Precedence Arrangement (ADPF) No. 347, has the capacity to promote and protect human rights, especially regarding separation. emphasizing the context of Brazil’s prison system, which is undergoing crisis and deserves to be studied carefully. To this end, it will use the deductive method and theoretical research, based on bibliographic review and statistical data released by the National Council of Justice (CNJ) of 2018 which shows the condition of vulnerability that the segregated are, exsurging the intervention by the judiciary as a mitigator and / or guarantor of constitutional precepts.